John Adams under fire : the Founding Father's fight for justice in the Boston Massacre murder trial - Abrams, Dan, 1966-; Fisher, David, 1946- (Hanover Square Press, 2020)
History remembers John Adams as a Founding Father and our country<U+2019>s second president. But in the tense years before the American Revolution, he was still just a lawyer, fighting for justice in one of the most explosive murder trials of the era. On the night of March 5, 1770, shots were fired by British soldiers on the streets of Boston, killing five civilians. The Boston Massacre has often been called the first shots of the American Revolution. As John Adams would later remember, On that night the formation of American independence was born. Yet when the British soldiers faced trial, the young lawyer Adams was determined that they receive a fair one. He volunteered to represent them, keeping the peace in a powder keg of a colony, and in the process created some of the foundations of what would become United States law. In this book, New York Times bestselling authors Dan Abrams and David Fisher draw on the trial transcript, using Adams<U+2019>s own words to transport readers to colonial Boston, a city roiling with rebellion, where British military forces and American colonists lived side by side, waiting for the spark that would start a war.